1997
DOI: 10.1093/bja/79.4.446
|View full text |Cite
|
Sign up to set email alerts
|

Does the addition of clonidine affect duration of analgesia of bupivacaine wound infiltration in inguinal hernia surgery?

Abstract: We conducted a prospective, randomized, doubleblind study to compare analgesia obtained by wound infiltration using 29 ml of 0.25% bupivacaine alone, or with the addition of clonidine hydrochloride 150 g. A third group received bupivacaine wound infiltration with clonidine 150 g i.m. to control for the systemic effects caused by absorption of clonidine. We studied 46 adults undergoing elective inguinal hernia repair. The general anaesthetic technique, postoperative analgesia and wound infiltration technique we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 11 publications
0
22
0
2
Order By: Relevance
“…The use of clonidine as an adjuvant to wound infiltration with local anaesthetics prior to elective hernia surgery has been cited in literature [11]. Doses up to 150 lg added to 0.5 % bupivacaine for wound infiltration did not reveal any improvement in duration of postoperative analgesia, though initial pain scores in the postoperative period were seen to be better in these patients.…”
Section: Discussionmentioning
confidence: 96%
“…The use of clonidine as an adjuvant to wound infiltration with local anaesthetics prior to elective hernia surgery has been cited in literature [11]. Doses up to 150 lg added to 0.5 % bupivacaine for wound infiltration did not reveal any improvement in duration of postoperative analgesia, though initial pain scores in the postoperative period were seen to be better in these patients.…”
Section: Discussionmentioning
confidence: 96%
“…α 2 agonists are safely used through various routes with promising effect as they prolong the duration of sensory and motor blockade, induced by local anesthetics irrespective of route of administration. [6][7][8] We had used clonidine and dexmedetomidine in a safe allowable doses to get maximum benefit. Keplinger et al studied different doses of dexmedetomidine with local anesthetics for peripheral nerve block, and found significant dose-dependent increase in the mean duration of analgesia [9] and Singelyn et al reported that a minimum dose of clonidine (0.5 µg/kg) added to mepivacaine prolongs the duration of anesthesia and analgesia in brachial plexus block.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Our study was based on hypothesis that α 2 agonists as an adjuvant enhance the quality of block. [6][7][8] As there is a scarcity of studies comparing dexmedetomidine and clonidine in various doses, we compared dexmedetomidine 1 µg/kg and clonidine 1.5 µg/kg as adjuvants in supraclavicular brachial plexus block.…”
Section: Introductionmentioning
confidence: 99%
“…The LA was injected into various layers of the surgical wound: under the fascia, 3,5 subcutaneously 11 and into the edges of the wound, 2,3,6,8-10 subcutaneously and into the muscle. 12 When added to the LA and used in single doses, NSAIDs 13 and clonidine 10 did not significantly prolong the duration of analgesia.…”
Section: Microbiological Analysis Of Catheter Tips and Wound Healingmentioning
confidence: 90%